Compound Heterozygosity for a Novel Mutation Codon 104 (–A) (HBB: c.313delA) and Codons 41/42 (–CTTT) (HBB: c.126_129delCTTT) Leading to β-Thalassemia Major in a Chinese Family. (1st November 2020) - Qiu, Yuling; Huang, Yuanyuan; Chen, Ping; Wei, Shilu; Su, Qisheng; Zhang, Zunni; Yang, Zheng; Ye, Lihua; Huang, Jun; Shen, Xuelian; Mo, Wuning
Abstract: β-Thalassemia (β-thal) is a hereditary blood disorder characterized by the reduced or absent synthesis of β-globin chains. Here, we report a case of severe thalassemia with compound heterozygosity for a novel deletion mutation at codon 104 (–A) ( HBB : c.313delA) and codons 41/42 (–CTTT) ( HBB : c.126_129delCTTT) on the β-globin gene ( HBB ), and a coinheritance of the –α 4.2 (leftward) deletion on the α-globin gene cluster. The proband was a 12-year-old boy, and four other family members were involved in this study. This novel frameshift mutation caused classical β-thal trait in the heterozygote and a transfusion-dependent form of β-thal major (β-TM) in compound heterozygosity with other β 0 mutations.